Access to and consumption of natural gas: Spatial and socio-demographic drivers. (August 2020) - Curtis, John; Tovar, Miguel Angel; Grilli, Gianluca
Abstract: This research examines fuel choice for residential heating, with a particular focus on switching to natural gas from carbon intensive alternatives. In the context of reducing greenhouse gas emissions in the residential sector, fuel switching from coal and oil to natural gas for space heating is assessed as a potential policy option using Ireland as a case study. A range of building attributes and household characteristics are associated with fuel choice for household space heating, including distance to the gas network, which is inversely associated with the probability of gas connection. Distance decay effects are likely attributed to network connection fees, which are proportional to the connection distance. The impact of setting the marginal connection cost associated with distance to zero are simulated to examine emission and expenditure impacts across socio-economic groups. Up to 13% of unconnected properties are likely to respond to such an incentive, yielding a 3.9% reduction in greenhouse gas emissions and a 1.5% reduction in fuel expenditure relative to pre-policy levels of unconnected households within the study. Expenditure and emission impacts differ across socio-economic groups with the largest reductions expected to occur among semi-skilled/unskilled households, which are frequently among the least affluent households. Highlights: Examines primary residential heating fuel choice. With a particular focus on switching to gas & effect of network connection fees. Simulates effect of flat-rate connection fee for gas connections and emissions. Results: reduction in both emissions and household fuel expenditure. Discounted value of emissions savings offsets loss in connection fee revenue.